The Enigma of Community Responsibility: Ethical Reflections on Accident Compensation - Gaskins, Richard (Victoria University of Wellington Law Review, 2015)
Lurking behind the familiar ACC principle of "community responsibility" are some core questions about what it means to be a community, and how responsibility is to be assigned. The original ACC blueprint took a distinctive approach to both terms – which was diluted in the process of implementation and further weakened in successive legislative amendments. And yet, mysteriously, over five decades, the language of "community responsibility" has remained at the centre of ACC policy discourse. Reflecting on ethical presumptions can clarify these evolving meanings, reframing key questions for future ACC debates.